Experimental investigation on laminar heat transfer performances of RP-3 at supercritical pressure in the helical coiled tube. (April 2022) - Lei, Zhiliang; Bao, Zewei
Highlights: Heat transfer correlations of RP-3 are established in the helical coiled tube. Correlations include the parameters of density, specific heat and grashof number. Re, Nu, and centrifugal richardson number increase exponentially along the tube. Experimental data for various fuels and structures are used to verify the correlation. Abstract: The laminar heat transfer characteristics of RP-3 in the liquid phase and supercritical phase were experimentally studied at 5 MPa in the helical coiled tubes. The influences of secondary flow and buoyancy on heat transfer were analyzed under different heat fluxes, mass flow rates and helical diameters. The Nu increased with the increase of curvature. When the heat flux was 150 kW/m 2, the mass flow rate was 1 g/s, and the wall temperature was higher than the critical temperature, the Re, Nu, and centrifugal Richardson number increased exponentially along the tube length. By introducing the combined parameters of density, specific heat and Grashof number, the correlations of RP-3 were established in the helical coiled tube under supercritical laminar mixed convection. In addition, the experimental data under different fuels, helical diameters and tube diameters were used to verify the above correlation.